A Theory of Intraday Patterns: Volume and Price Variability - Admati, Anat R.; Pfleiderer, Paul (Review of Financial Studies, 1988)
This article develops a theory in which concentrated-trading patterns arise endogenously as a result of the strategic behavior of liquidity traders and informed traders. Our results provide a partial explanation for some of the recent empirical findings concerning the patterns of volume and price variability in intraday transaction data.